Identification and characterization of marine pathogenic vibrios in cultured golden pompano (Trachinotus ovatus) in Guangxi, China - Qing Yu#; Mingzhu Liu#; Fei Li; Yibing Wang; Zijun Lu; Siting Wu; Xianling Qin; Xianyun Chen; Deqiang Shi; Lantian Lu; Ke Ke; Qiwei Qin; et al. (Annals of Marine Science - Peertechz Publications, 2018)
Vibriosis has caused great economic losses to marine aquaculture with high mortality worldwide.Guangxi province is an important cultured center for tropical marine fi sh species in South China. However, no research focused on epidemiological characterization of vibriosis in golden pompano aquaculturein Guangxi province have been carried out. We isolated and identifi ed the strains of V. harveyi causedthe serious disease that occurred in cultured golden pompano in Guangxi province, by biochemical and physiological tests, and PCR. A cell line derived from the brain of golden pompano Trachinotus ovatus (TOGB) had been established and characterized in the previous study, was applied to analyze the cytotoxicities of extracellular products (ECPs) from GT-V. harveyi isolates. We also proved that GT-V. harveyi isolates produced cytotoxic effects in vivo. This study identifi ed the vibriosis outbreaks in golden pompano aquaculture in Guangxi province this year.